1997
DOI: 10.1021/ma9617577
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Dielectric Behavior of a Styrene−Isoprene−Styrene Triblock Copolymer in Selective Solvents. 2. Contribution of Loop-Type Middle Blocks to Elasticity and Plasticity

Abstract: Rheological and dielectric behavior was examined for concentrated solutions of a styreneisoprene-styrene (SIS) triblock copolymer in monomeric and polymeric I-selective solvents, n-tetradecane (C14) and a low-M homopolyisoprene (I-1; M ) 1.4K). The I blocks had symmetrically once-inverted dipoles along the block contour, and their midpoint motion was dielectrically detected. The SIS solutions exhibited rubbery, plastic, and viscous behavior at low, intermediate, and high temperatures (T). Dielectric and viscoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(140 citation statements)
references
References 38 publications
(161 reference statements)
6
133
1
Order By: Relevance
“…The disordering of the network (T ODT ), on the other hand, sets-in at the crossover of G′ and G″. Both transitions can be interpreted in terms of the stability of the microstructure of the system [30][31][32][33]. In the plastic fluid regime, the polystyrene domains become softer and stress can cause the pullout of styrene blocks.…”
Section: Rheological Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The disordering of the network (T ODT ), on the other hand, sets-in at the crossover of G′ and G″. Both transitions can be interpreted in terms of the stability of the microstructure of the system [30][31][32][33]. In the plastic fluid regime, the polystyrene domains become softer and stress can cause the pullout of styrene blocks.…”
Section: Rheological Behaviourmentioning
confidence: 99%
“…Rheological studies [30][31][32][33][34] of polystyrene-poly(ethylene/butylene)-polystyrene (PS-PEB-PS) triblock copolymer gels showed that the gels are in a rubber-like viscoelastic state at ambient temperature, which means that the polystyrene domains act as permanent physical crosslinks. Above the glass transition temperature (T g ) of the PS nanodomains, there is a change from a rubbery gel to a plastic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)], the bridging chains produce an association, which can lead to phase-separated solutions at low polymer contents 2,4 and physical networks at high polymer contents. [5][6][7][8][9][10][11][12][13][14] Watanabe and coworkers 9,10 conducted extensive investigations of styrene-isoprene-styrene (SIS) triblocks in the midblock-selective solvent tetradecane at various polymer concentrations. The fraction of bridges was directly determined by an elegant dielectric technique and was shown to decrease as the triblock was diluted.…”
Section: Introductionmentioning
confidence: 99%
“…3 ) revealed the swelling of this block with C14 that decreased the glass transition temperature T g to 30 C. 13 At the same time, it should be emphasized that our PS block is longer and should have T g > 30 C to behave as a rigid (glassy) anchor for the PI corona at our experimental temperature, 25…”
Section: Viscoelastic and Saxs Datamentioning
confidence: 73%